2017
DOI: 10.1002/smll.201603695
|View full text |Cite
|
Sign up to set email alerts
|

Bent Polytypic ZnSe and CdSe Nanowires Probed by Photoluminescence

Abstract: Nanowires (NWs) have witnessed tremendous development over the past two decades owing to their varying potential applications. Semiconductor NWs often contain stacking faults due to the presence of coexisting phases, which frequently hampers their use. Herein, it is investigated how stacking faults affect the optical properties of bent ZnSe and CdSe NWs, which are synthesized using the vapor transport method. Polytypic zinc blende-wurtzite structures are produced for both these NWs by altering the growth condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…It has been observed that the emission of bent (or buckled) NWs red shifts due to a piezoelectric field. 913 We predict that the band gap of the bent GaP and GaAs NWs would decrease owing to the dominant tensile strain. Furthermore, the larger excessive tensile strain of GaAs NWs suggests the larger band gap decrease as compared to that of GaP NWs.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the emission of bent (or buckled) NWs red shifts due to a piezoelectric field. 913 We predict that the band gap of the bent GaP and GaAs NWs would decrease owing to the dominant tensile strain. Furthermore, the larger excessive tensile strain of GaAs NWs suggests the larger band gap decrease as compared to that of GaP NWs.…”
Section: Results and Discussionmentioning
confidence: 99%
“…28 For bent (or buckled) NWs, a red-shifted emission has been observed, which has been explained by the piezotronic effect, in which under a piezoelectric field, the number of photons emitted from the outer surface of the NW is much larger than that from the inner surface. 913 The outstanding piezoelectric properties of ZnO and CdS NWs have facilitated the development of various piezotronic and piezo-phototronic devices such as nanogenerators, field-effect transistors, and light-emitting diodes, which rely on the piezoelectric potential created along the strained NWs. 3,1416 Moreover, the enhanced carrier mobility or photocurrent of strained NWs has attracted widespread research interest owing to their great potential in a rich variety of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Different materials in the II‐VI compound have different bandgaps, such as 1.5 eV for CdTe, 3.7 eV for ZnS, and the like. This makes them ideal for optoelectronic devices at different wavelengths . ZnO is one of the most widely studied materials in oxide semiconductors (II‐VI) .…”
Section: Low‐dimensional Semiconductor Nanomaterialsmentioning
confidence: 99%
“…This makes them ideal for optoelectronic devices at different wavelengths. 101,102 ZnO is one of the most widely studied materials in oxide semiconductors (II-VI). 66,92,103-107 ZnO has very good semiconductor properties with wide direct bandgap and unique piezoelectric and mechanical properties, which make ZnO have many applications, such as PDs, solar photovoltaics, flexible electronics, and so on.…”
Section: D Materialsmentioning
confidence: 99%
“…Zinc selenide (ZnSe) is an important II-VI semiconductor material with a direct band-gap of ~2.7 eV at room temperature, which is widely regarded as a very good candidate for blue-violet light emitting devices [1] [2] [3] [4]. With the miniaturization of devices, many research groups have begun to study the nanostructures of ZnSe materials and have done a lot of work in this area.…”
Section: Introductionmentioning
confidence: 99%